MENELAAH NILAI MORAL DALAM NOVEL HUJAN KARYA TERE LIYE:KAJIAN SASTRA STRUKTUAL - Elsy Olivia; Ria; Aisyah Fitri; Kumala Dewi; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The novel Hujan by Tere Liye not only presents an engaging story about love, loss, and environmental change, but also contains various profound moral values. This study employs a structural literary approach to analyze the relationship between the intrinsic elements of the novel and the moral values contained within it. The purpose of this research is to describe the intrinsic elements of the novel Hujan and to identify the moral values conveyed by the author through the story. The method used is descriptive-analytical with data collection techniques in the form of literature study, intensive reading, note-taking, and data classification. The results show that intrinsic elements such as theme, characters and characterization, plot, setting, point of view, and language style work synergistically to construct the moral messages in the novel. The moral values found include perseverance, empathy, sacrifice, faith, responsibility, and environmental awareness. This study confirms that the novel Hujan functions not only as entertainment, but also as a medium for moral learning for readers.